Protocolo de desmame para redução do tempo de ventilação mecânica em crianças internadas em Unidades de Terapia Intensiva Pediátrica: Revisão Sistemática e Metanálise - Almeida, Suzana Cristina (2024)
In Pediatric Intensive Care Units (PICU), invasive mechanical ventilation (IMV) is required for most children and teenagers. Although important, IMV can predispose patients to adverse events, making ventilatory weaning necessary as soon as possible. The appropriate timing for starting the weaning process and performing extubation is still uncertain in pediatrics, and there is no consensus on the best timing and methods. Using a protocol can outline best practices and assist in this process. Therefore, this review study aims to identify whether the implementation of a weaning protocol in the PICU, compared to standard treatment, can reduce the duration of IMV, length of stay in the PICU and hospital, and adverse events such as extubation failure, unplanned extubation, tracheostomy, mortality, and functional decline in children and adolescents. Methods: PubMed, EMBASE, CINAHL, Web of Science, and Cochrane Central Register of Controlled Trials, were searched in July 2023 and updated twice in February and October 2024. The research strategy and article selection were developed using the PICOS format. Randomized controlled trials were included if the intervention involved a weaning protocol compared to standard care in children over 28 days and under 18 years of age, using IMV, and admitted to the PICU. Two authors selected articles for eligibility, extracted data, and assessed the risk of bias and certainty of evidence. The primary outcome was the duration of IMV. Secondary outcomes included the duration of PICU and hospital stay, use of non-invasive ventilation after extubation, and adverse events such as unplanned extubation, extubation failure, tracheostomy, hospital mortality, and functional decline. Results: Eight trials were included (n = 11,822). The most often weaning protocol's techniques employed were the spontaneous breathing tests and daily readiness screenings. The length of IMV was not shortened by the weaning protocol (MD -0.01 days; 95% CI -0.16 to 0.13; moderate-certainty evidence). The extubation failure was reduced in 13% with weaning protocol (RR 0.87; 95% CI, 0.65 to 1.17; moderate-certainty evidence). The subgroup analysis showed that the weaning protocol decreases the hospital LOS (MD -2.39 days; 95% CI, -3.48 to -1.31; high-certainty evidence) and tracheostomy (RR 0.46; 95% CI, 0.25 to 0.84), and a non-significant but relevant reduction in mortality (RR 0.81; 95% CI, 0.60 to 1.11; moderate-certainty evidence) and unplanned extubation (RR 0.71; 95% CI, 0.48 to 1.04) in the subgroup of patients intubated for respiratory disease. Conclusions: The implementation of a weaning protocol has shown positive results, including a significant reduction in hospital stay and need for tracheostomy after extubation failure for patients intubated due to respiratory disease, a clinically relevant reduction in mortality and unplanned extubation for these patients, and a clinically relevant decrease in the risk of extubation failure. However, the protocol had no impact on the duration of mechanical ventilation, or the time spent in the PICU.